Exploring the Determinant of Business Students’ Sustainability Behavior - Budi Hartono Kusuma; Sri Sundari; Kartini Kartini (Universitas Kristen Maranatha, 2026)
Purpose – This study aims to empirically prove the positive influence of (1) self-transcendence values ​​on the intention to engage in sustainability accounting, (2) intention to engage in sustainability accounting on sustainability behavior, and (3) self-transcendence values ​​on sustainability behavior through intention to engage in sustainability accounting. Design/Methodology/Approach – Data were collected through an online questionnaire survey. The respondents were students from the Faculty of Economics and Business. Hypothesis testing used partial least squares structural equation modeling with WarpPLS version 8.0 software. Results – This study successfully demonstrated that self-transcendence values ​​are a determinant of intention to engage in sustainability accounting and also sustainability behavior. Furthermore, the intention to engage in sustainability accounting has been shown to have a positive impact on sustainability behavior. Research limitations/Implications – This research has implications for higher education in Indonesia, emphasizing the importance of understanding the factors shaping students' sustainability behavior. Higher education institutions need to instill in their students the importance of upholding and living their personal values. Keywords: Business Students, Self-Transcendence Values, Sustainability Accounting, Sustainability Behavior